2022
DOI: 10.3390/children9060878
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Pilot Study on the Effects of Thermal Ablation on Lamb Growth Plates

Abstract: (1) Background: Thermal ablation has been demonstrated to affect the bone growth of osteoid osteoma in adolescents. Growth modulation due to thermal heat in children is conceivable, but has not yet been established. We used lamb extremities as a preclinical model to examine the effect of thermal ablation on growth plates in order to evaluate its potential for axial or longitudinal growth modulation in pediatric patients. (2) Methods: Thermal ablation was performed by electrocautery on eight different growth pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Jackle et al presented findings suggesting that thermoablation can be used as a minimally invasive method to eliminate OO localised to different areas of the epiphyseal cartilage. A study in lambs indicated only localised tissue damage [ 76 ].…”
Section: Treatment Of Atypical Osteoid Osteomasmentioning
confidence: 99%
“…Jackle et al presented findings suggesting that thermoablation can be used as a minimally invasive method to eliminate OO localised to different areas of the epiphyseal cartilage. A study in lambs indicated only localised tissue damage [ 76 ].…”
Section: Treatment Of Atypical Osteoid Osteomasmentioning
confidence: 99%